Las disciplinas científicas como encrucijadas de saberes: el caso de los estudios de Biblioteconomía y Documentación en las universidades españolas. - García Zorita, Carlos (Revista General de Información y Documentación, 2001)
TUs article analyses interdisciplinarity in the area of Library and Infor mation Science, on the grounds of the participation of other disciplines in the curricula established by in Spanish universities for studies towards degrees and associate degrees in this area of knowledge. To conduct the study, the authors analysed the resolutions approving the curricula br associate degrees in Libra rianship and Documentation and degrees in Documentation published in the Spanish Oflicial State Journal (ROE.). Multi-dimensional indicators were applied to the data obtained to draw maps, subsequently used to determine each university's profile in terms of the weight of each discipline in the overalí edu cational content. 167 Elías Sanz-Casado. Carlos García-Zorita... Las disciplinas científicas cotno ent.n¿cijada...
Keywords: lnterdisciplinarity; Curricula; Library and Information Science; Multi dimensional indicators